AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN FINDING THE CHARACTER VALUES OF NARRATIVE TEXT AT MA MUHAMMADIYAH BENGKULU - Herlina herlina; Melati Melati (Edu-Ling: Journal of English Education and Linguistics, 2020)
The researcher found that the students still had difficulties in finding character value, problem and difficulties with previous knowledge and metacognition in preliminary research. Therefore, objective of this research is to identify the factors that cause students’ difficulties in finding character value of narrative text. The method used in this research was descriptive qualitative. The subject of this research was students of XI MA Muhammadiyah Bengkulu, who had the lowest score in preliminary research. The technique of collecting data was by analyzing interview and giving questionnaire to the students. The result showed the factors that causes students’ difficulties in finding character value were exception in the decoding process, previous knowledge, motivation or perseverance, high level cognitive skills and metacognition. Based on the result of questionnaire, it can be concluded that most of students were fluent because they often read narrative text, so they can read the text in English easily. Then, most of students had problem in their previous knowledge, so they felt difficult to determine the character value. Although most of students do not have problems in motivation or perseverance because they like to read narrative text, they do not know how to find the character value in narrative text because they do not understand the story, so they felt difficult to determine the character value. Furthermore, most of students have problems in their metacognition, because they must read the narrative text repeatedly to determine the character value. In short, they must summarize the narrative text to determine the character value, because they felt difficult to determine the character value if they do not summarize the text.